Information and market power in DeFi intermediation - Pablo Azar; Adrian Casillas; Maryam Farboodi (Federal Reserve Bank of New York, 2024)
The decentralized nature of blockchain markets has given rise to a complex and highly heterogeneous market structure, gaining increasing importance as traditional and decentralized (DeFi) finance become more interconnected. This paper introduces the DeFi intermediation chain and provides theoretical and empirical evidence for private information as a key determinant of intermediation rents. We propose a repeated bargaining model that predicts that profit share of Ethereum market participants is positively correlated with their private information, and employ a novel instrumental variable approach to show that a 1 percent increase in the value of intermediaries' private information leads to a 1.4 percent increase in their profit share.
Keywords: G23; D82; L14; L22; G14; D43; 330; financial intermediation; oligopoly; blockchain; decentralized finance; cybersecurity